2020
DOI: 10.1088/1361-6463/ab7797
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric microplasma based binary Pt3Co nanoflowers synthesis

Abstract: The atmospheric microplasma in the gas-liquid phase technique serves as a new potential efficient and green catalyst preparation technique to fabricate nanomaterials. Due to the presence of diverse reactive species, this technique can promote rapid complex reactions in solutions, which are typically sluggish in traditional chemical processes. Here, atmospheric microplasma induced liquid chemistry (AMILC) is applied to fabricate three-dimensional (3D) binary Pt3Co nanoflowers. Nano-architectures of Pt3Co bimeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Alloy nanoflowers are a recent research topic, with publications dating back to only 10 years; approximately 20–30 studies have been reported on Au-, Pt-, Pd-, Ni-, Mo-, and Ir-based alloy nanoflowers. The nanoflowers have been synthesized by various reduction methods, 341,342,354,355,361 the AMILC method, 352 solvothermal methods, 70,350,353,360 and so on. 115,116,336,357 Alloy nanoflowers primarily exhibit potential applications as electrocatalysts for water splitting and fuel cells (Tables 15–17) due to their alloy and synergistic effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alloy nanoflowers are a recent research topic, with publications dating back to only 10 years; approximately 20–30 studies have been reported on Au-, Pt-, Pd-, Ni-, Mo-, and Ir-based alloy nanoflowers. The nanoflowers have been synthesized by various reduction methods, 341,342,354,355,361 the AMILC method, 352 solvothermal methods, 70,350,353,360 and so on. 115,116,336,357 Alloy nanoflowers primarily exhibit potential applications as electrocatalysts for water splitting and fuel cells (Tables 15–17) due to their alloy and synergistic effects.…”
Section: Discussionmentioning
confidence: 99%
“…A novel atmospheric microplasma induced liquid chemistry (AMILC) method has been applied for the controlled synthesis of 2D and 3D binary Pt 3 Co nanoflowers by Wang et al 352 As shown in the atmospheric microplasma (AMP) setup in Fig. 14 , the electrolyte consists of 0.002 M chloroplatinic acid hydrate (H 2 PtCl 6 · x H 2 O), 0.5 M sodium sulfate (Na 2 SO 4 ), and variable molar concentrations of cobalt( ii ) sulfate heptahydrate (CoSO 4 ·7H 2 O) dissolved in distilled water (40 mL).…”
Section: Synthesis Methods and Characterization Of Inorganic Nanoflowersmentioning
confidence: 99%
See 1 more Smart Citation